Teaching young children : an introduction - Henniger, Michael L. (Upper Saddle River, N.J. : Merrill, 1999)
Introduction to the field. Foundations. Organizing for instruction. The curriculum.
Keywords: Education; Early childhood education; Education -- Education, childhood -- Case studies